Effects of aponeurotomy on mechanics of muscle with intact neighboring muscular and nonmuscular structures - Yaman, Bora. (Thesis (M.S.)-Bogazici University. Institute of Biomedical Engineering, 2008., 2008)
Aponeurotomy (AT) is a surgical technique used to lengthen spastic and/or short muscles. In previous studies, the biomechanical effects of AT were studied both experimentally and by finite element modeling in isolated muscle. In this study, the aim is to determine the effects of AT on mechanics of muscle with intact neighboring muscular and non-muscular structures. In order to achieve this goal AT was performed on the proximal aponeurosis of extensor digitorum longus (EDL) muscle of rat. Length–isometric force characteristics of EDL distally and proximally as well as the tibialis anterior (TA) and extensor hallucis longus (EHL) muscle complex distally were determined in (1) the intact condition, (2) the acute AT condition (after partial fasciotomy and proximal aponeurotomy), (3) the post AT condition (i.e. repeating the second step), (4) the fasciotomy condition and (5) TA+EHL removal condition. EDL distal and proximal length-force characteristics were altered significantly after all surgical interventions. EDL distal forces at optimum muscle length were decreased by 34.8 % in post AT, 41 % in fasciotomy and 52 % in TA+EHL removal conditions compared to intact condition. Also muscle optimum length shifted to higher lengths by 0.53 mm in post AT, 0.66 mm in fasciotomy and 0.28 mm in TA+EHL removal conditions. EDL proximal forces at optimum muscle length were decreased by 42.2 % in post AT, 43.4 % in fasciotomy and 48 % in TA+EHL removal conditions compared to intact condition. For short lengths drop of muscle force after AT was more pronounced and muscle force decreased by 73 % in post AT condition. TA+EHL forces decreased gradually as EDL was lengthened distally. Besides this after each intervention overall TA+EHL force decreased. It is concluded that the presence of epimuscular connections limits the effects of aponeurotomy and it should be noted that before planning a surgery to restore the motion of a joint, the possible effects on the other end of the muscle and the synergetic muscles should be taken into account.
Keywords: Muscle strength.